ifo World Economic Survey November 2018 - Dorine Boumans; Johanna Garnitz (ifo World Economic Survey, 2018)
World Economic Climate: ifo World Economic Climate Deteriorates Further - Advanced Economies: The Economic Climate in the Advanced Economies Stabilises at a Satisfactory Level - Emerging and Developing Economies: Economic Climate in Emerging Market and Developing Economies Cools Down Further - Special Topic: Collective Memories on the European Debt Crisis -
Keywords: 330